Integrasi Teknologi dalam Pendidikan Sekolah Dasar sebagai Upaya Peningkatkan Literasi - Hatmoko, Fajar Tri; Rochmat, Syaiful; Siswanto, Deny Hadi; Pisriwati, Siti Atwano (Prodi PGMI STAI Sabili Bandung, 2024)
This study aims to analyze the role of technology to improve literacy of students with special needs. Technology has great potential to support more adaptive and personalized learning. The method used in this study is a survey with a qualitative approach. The research sample included Muhammadiyah Elementary Schools in Mlati District, Sleman Regency and the instruments used consisted of closed questionnaires and semi-structured interviews to collect data related to the use of technology in learning. Data were analyzed using descriptive statistical techniques and regression tests. The results of the study indicate that technology integration, such as adaptive learning applications, digital assistive devices, and e-learning platforms, is effective in improving student literacy, both basic and digital literacy. The conclusion of this study is that technology has an important role in education, with a significant impact on improving students' literacy skills. Therefore, it is recommended that the government and educational institutions continue to support the use of technology in education through training teachers and providing appropriate devices